L’église Saint‑Pierre de La Romieu (Gers), nouvelle interprétation - Jacques Dubois (Les Cahiers de Framespa)
The former collegiate church of Saint‑Pierre de La Romieu (Gers), built around 1312‑1320/1321 by Cardinal Arnaud d’Aux, is a vast architectural complex that includes a single‑nave church, a cloister to the north‑west, and two towers, one octagonal associated with the apse, the other, to the north‑west, square, which serves as a bell tower. Until today, historiography has considered it as part of the same project. However, several arrangements raise questions, while the study of the building shows that the church and octagonal tower were built first and that the construction of the cloister and bell tower was undertaken in a second phase when the prelate founded, in 1318, a collegiate church for funerary purposes. The first construction site then corresponds to a project distinct from that of the collegiate church which makes sense when the neighboring palace of the prelate and the circulations between the church and the cardinal’s residence are taken into account, while the second one responds to the adaptations required by the presence of a college of canons.